A topologically substituted boron nitride hybrid aerogel for highly selective CO2 uptake - Kutty, Rajendrannair Govindan (2020)
A topologically mediated synthesis of porous boron nitride aerogel has been experimentally and theoretically investigated for carbon dioxide (CO2) uptake. Replacement of the carbon atoms in a precursor aerogel of graphene oxide and carbon nanotubes was achieved using an elemental substitution reaction, to obtain a boron and nitrogen framework. The newly prepared BN aerogel possessed a specific surface area of 716.56 m2/g and exhibited an unprecedented twentyfold increase in CO2 uptake over N2, adsorbing 100 cc/g at 273 K and 80 cc/g in ambient conditions, as verified by adsorption isotherms via the multipoint Brunauer-Emmett-Teller (BET) method. Density functional theory calculations were performed to give hints on the mechanism of such high selectivity of CO2 over N2 adsorption in BN aerogel, which may be due to the interaction between the intrinsic polar nature of B–N bonds and the high quadrupole moment of CO2 over N2.